Предмет: Алгебра,
автор: anastasia157n
Упростите выражение
1)(4a-b)(a-6b)+a(25b-3a) 2) (2x+3y)(x-y)-x(x+y) 3)3a(a+1)+(a+2)(a-3) 4) 2c(5c-3)-(c-2)(c-4
Ответы
Автор ответа:
0
1) (4a-b)(a-6b)+a(25b-3a)=4a²-24ab-ab+6b²+25ab-3a²=
4a²-25ab+25ab+6b²-3a²=4a²-3a²+6b²=a²+6b²
2) (2x+3y)(x-y)-x(x+y)=2x²-2xy+3xy-3y²-x²-xy=2x²-x²-3y²=x²-3y²
3) 3a(a+1)+(a+2)(a-3)=3a²+3a+a²-3a+2a-6=4a²+2a-6
4) 2c(5c-3)-(c-2)(c-4)=10c²-6c-c²+4c+2c-8=9c²-6c+4c+2c-8=9c²-8
4a²-25ab+25ab+6b²-3a²=4a²-3a²+6b²=a²+6b²
2) (2x+3y)(x-y)-x(x+y)=2x²-2xy+3xy-3y²-x²-xy=2x²-x²-3y²=x²-3y²
3) 3a(a+1)+(a+2)(a-3)=3a²+3a+a²-3a+2a-6=4a²+2a-6
4) 2c(5c-3)-(c-2)(c-4)=10c²-6c-c²+4c+2c-8=9c²-6c+4c+2c-8=9c²-8
Похожие вопросы
Предмет: Русский язык,
автор: vladazukova018
Предмет: Математика,
автор: aida773
Предмет: История,
автор: amirbekovaajsha1
Предмет: Математика,
автор: nnl73